ASUPAN MIKRONUTISI IBU HAMIL, MENYUSUI DAN STATUS GIZI ANAK: ANALISIS BIBLIOMETRIK: Maternal and breastfeeding mother’s micronutrient intake and child’s nutrition status: a bibliometric analysis - Apriningsih Apriningsih; Rita Ismail; Yessi Crosita Octaria (Poltekkes Kemenkes Yogyakarta, 2025)
ABSTRACT Many studies have been conducted on child nutrition, including its determinants. To improve understanding of child nutritional status, a bibliometric analysis of maternal micronutrient intake during pregnancy and lactation and child nutritional status was conducted. This analysis aimed to identify key trends and potential areas for future research. The bibliometric analysis was conducted using Biblioshiny software supported by